Assessing Work-Related Burnout and Job Satisfaction among Obstetrics and Gynecology Residency Program Coordinators - Ofei-Dodoo, Samuel; Irwin, Gretchen; Kuhlmann, Zachary; Kellerman, Rick; Wright-Haviland, Stacey; Dreiling, Michaela (Kansas Journal of Medicine, 2019)
Introduction. This study explored the prevalence of and the relationship between job satisfaction and burnout among obstetrics and gynecology residency program coordinators. Methods.xThis cross-sectional study involved members of the American Program Managers of Obstetrics and Gynecology. The Copenhagen Burnout Inventory and Spector’s Job Satisfaction Survey were used to measure the participants’ burnout and job satisfaction rates respectively. Data were collected between August 2017 and December 2017. The authors used Fisher’s exact tests, Spearman’s r correlations, and multiple linear regression to analyze the data. Results. There was an 83% (171/207) response rate. Thirteen percent of the coordinators reported high, 70% moderate, and 17% low job satisfaction scores. Thirty-nine percent of the coordinators reported high, 25% moderate, and 36% slight work-related burnout rates. Correlation coefficient showed a significantly negative relationship between job satisfaction and work-rated burnout, (rs[169] = -0.402, p < 0.01). Regression analysis showed co-workers (β = -0.47) and supervision (β = -0.16) domains of the job satisfaction scale were significant predictors of work-related burnout (R = 0.55; F[5, 195] = 11.05; p < .001). Conclusions. The findings highlight the importance of job satisfaction factors, such as support from coworkers and supervisors, in dealing with work-related burnout among residency coordinators. Kans J Med 2019;12(1):11-16.